(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
This article analyzes ways to improve strategic management in joint-stock companies based on the experience of foreign countries. The article uses the experience of developed countries such as the United States, Japan, Germany, and also examines the possibilities of their application in the conditions of Uzbekistan.